IMPLEMENTASI PROGRAM DAILY ACTVITIES BERBASIS NILAI-NILAI KARAKTER FATHIA DALAM MEMBINA WATAK KEWARGANEGARAAN SISWA SEKOLAH DASAR - Septiana, Tina (Universitas Pendidikan Indonesia, 2017)
The results of the research showed the implementation of FATHIA character values such as moral values, spiritual, love the environment, honesty, faith, leadership, intellegency, dinamic, superior, helper, creative, and tolerant. The good characters are shown through positive habituation in daily activities program based on FATHIA character values without any force. Thus, it indicated that the implementation of daily activities program in the school is really successful. There are some reccomendations for further research as The implementation of FATHIA character values through the daily activities program (habituation) and the cooperation between teacher, school, and parent are needed, so that it can build the whole implementations of FATHIA character values (civic disposition) among the students.